Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/s0387-7604(03)00170-0
|View full text |Cite
|
Sign up to set email alerts
|

The metaphor and sarcasm scenario test: a new instrument to help differentiate high functioning pervasive developmental disorder from attention deficit/hyperactivity disorder

Abstract: It is sometimes difficult to discriminate high functioning pervasive developmental disorders (HFPDD) from attention deficit/hyperactivity disorders (AD/HD) in young children because of the behavioral similarities between the two. For adequate diagnosis, understanding fundamental differences in their social cognitive abilities might become significant. In order to detect the differences in social cognitive abilities between AD/HD and HFPDD, a new test, the Metaphor and Sarcasm Scenario Test (MSST) was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 15 publications
3
61
1
2
Order By: Relevance
“…The Ethics Board of the Gunma University School of Health Sciences approved all procedures (No. [21][22][23][24][25][26], and written informed consent was obtained from all the participants.…”
Section: Participantmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ethics Board of the Gunma University School of Health Sciences approved all procedures (No. [21][22][23][24][25][26], and written informed consent was obtained from all the participants.…”
Section: Participantmentioning
confidence: 99%
“…22 This test consists of 5 metaphoric and 5 sarcastic sentences; metaphoric sentences are odd numbered and sarcastic sentences even. The words and sentences in MSST were selected from standard textbooks of Japanese language (Mitsumura Press) for 1st, 2nd, and 3rd grades in elementary school.…”
Section: Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the interpretive skills required for irony appreciation are some of the skills thought to be particularly problematic for individuals with ASD (Happé 1993;Losh and Capps 2006). Several studies have now shown that some individuals with ASD have deficits in irony comprehension compared to their typically-developing peers (Adachi et al 2004;Kaland et al 2002;MacKay and Shaw, 2004;Martin and McDonald 2004;Wang et al 2006). For instance, in Kaland et al (2002), participants were presented with ironic remarks in the context of short stories and were asked ''Why did [ironic speaker] say that?''…”
mentioning
confidence: 99%
“…Participants with ASD were less accurate in their responses; that is, less frequent in detecting that the ironic speaker was joking. Given these specific deficits in irony interpretation, some researchers have argued that an irony comprehension task could be used to discriminate HFASD from other developmental disorders, such as ADHD (Adachi et al 2004).…”
mentioning
confidence: 99%